A biomimetic Setaria viridis-inspired imprinted nanoadsorbent: green synthesis and application to the highly selective and fast removal of sulfamethazine. Issue 12 (25th January 2016) - Ma, Ping; Zhou, Zhiping; Dai, Jiangdong; Qin, Ling; Ye, Xubo; Chen, Xiang; He, Jinsong; Xie, Atian; Yan, Yongsheng; Li, Chunxiang
Abstract : The preparation of biomimetic Setaria viridis -inspired hydrophilic magnetic imprinted nanoadsorbent, via a two-step surface-initiated ATRP in a green alcohol/water solvent at RT, with MHNTs used as nano-cores, was first reported. Abstract : Nowadays, it is very necessary to develop high-efficiency nanoadsorbents to remove drug contaminants from wastewater. Inspired by a biomimetic Setaria viridis -like structure, we provide a simple and general approach for the preparation of hydrophilic magnetic surface molecularly imprinted core–shell nanorods (HMMINs) via a two-step surface-initiated atom transfer radical polymerization in a green alcohol/water solvent mixture at room temperature, with magnetic halloysite nanotubes (HNTs, a hollow tubular structured natural clay mineral) used as nano-cores. HMMINs showed a well-defined core–shell structure with an ultra-thin imprinted film (12 nm) and hydrophilic polymer brushes (2–4 nm), where magnetic nanoparticles (11 nm) were uniformly dispersed onto the surface of halloysite nanotubes. HMMINs possess good magnetic properties and thermal stability. Surface grafting of the hydrophilic polymer brushes enhanced the adsorption selectivity and kinetics. HMMINs exhibited a large adsorption capacity (37.64 ± 1.36 μmol g −1 ) and fast kinetics (within 45 min) towards a typical antibiotic drug sulfamethazine (SMZ) from pure water. Adsorption isotherm and kinetics data were well described by the Freundlich isotherm model and pseudo-second-order kinetic equation, respectively. HMMINs displayed good selectivity towards SMZ as compared with other antibiotics, as well as good regeneration performance, providing a potentially practical application in the highly efficient and selective removal of antibiotic contaminants from wastewater.